Kebertahanan Subak di Era Globalisasi - Wayan Windia (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Basically subak is a farmer-managed irrigation system in Bali. It is an entity managing some sites of rice field, getting irrigation water from one source, having subak temple, and getting an autonomy of internally and externally. It also has some natural bounderies. Subak as a socio-cultural institution has some strengths. But subak is very weak because of external intervention. The globalization (competition, pragmatism, materialism, etc) highly influences the subak existence. Now, irrigation water for subak is taken by tourism sector as water drinking industry and by the domestic used. Therefore water for subak is limited. Also, the land tax (pajak bumi dan bangunan) is very high, because the number of tax is based on rice fileld location. That is why land conversion in Bali is very high, about 750 ha/year. The problems and threats of subak in Bali are coming from tourism sector, green revolution concept, free trade, and biotechnology development. To increase the defensiveness and sustainability of subak needs a strategic policy in relation with parhyangan (values) aspects, pawongan (social) aspects, and palemahan (physical) aspects.